The association of dietary nitrates/nitrites intake and the gut microbial metabolite trimethylamine N-oxide and kynurenine in adults: a population-based study - Mirzababaei, Atieh; Mahmoodi, Maryam; Abaj, Faezeh; Barkhidarian, Bahareh; Dehghani, Azadeh; Khalili, Pardis; Roumi, Zahra; Mirzaei, Khadijeh (Frontiers in Nutrition, 2024)
Background: Dietary nitrate and nitrite may affect gut microbiota and its metabolites, such as trimethylamine N-oxide (TMAO) and kynurenine (KYN). However, this association and the exact mechanism are still unclear. Therefore, this study aimed to assess the association between dietary consumption of nitrite and nitrate on TMAO and KYN levels in adults. Methods: This cross-sectional study was employed on a subsample baseline phase of Tehran University of Medical Sciences (TUMS) Employee’s Cohort study (TEC). 250 adults aged 18 years or over, were included in the current analysis. Data on the dietary intakes were collected using a validated dish-based food frequency questionnaire (FFQ) and dietary intakes of nitrite and nitrate were estimated using FFQ with 144 items. Serum profiles and TMAO and KYN were measured by standard protocol. Result: The findings of this study demonstrate a significant association between the intake of animal sources of nitrate and nitrite and the likelihood of having elevated levels of TMAO and KYN. Specifically, after adjustment, individuals with highest intake adherence to nitrates from animal sources exhibited increased odds of having the highest level of TMAO (≥51.02 pg/ml) with (OR=1.51, 95%CI=0.59-3.88, P=0.03) and KYN (≥417.41 pg/ml) with an (OR=1.75,95%CI=0.73-4.17, P=0.02). Additionally, subjects in the highest of animal intake from nitrite sources had 1.73- and 1.45-times higher odds of having the highest level of TMAO and KYN. These results emphasize the potential implications of animal-derived nitrate and nitrite consumption on the levels of TMAO and KYN. Conclusion: The present evidence indicates that a high level of nitrate and nitrite intake from animal sources can increase the odds of high levels of TMAO and KYN. Further studies suggest